CRN Application to Predict the NOx Emissions for Industrial Combustion Chamber - Thanh Hao, Nguyen; Jungkyu, Park (Asian Journal of Engineering and Applied Technology, 2013)
The development of chemical reactor network (CRN) models to predict the NOx emissions is very important for the modern combustion system design. In this study, the new chemical reactor network models are constructed based on the computational fluid dynamics (CFD) to simulate the burning process of the industrial combustor. The boundary and the operating conditions used for these CRN models reflect the typical operating conditions of the industrial combustor. The global mechanism has been developed by GRI 3.0 in the UW chemical reactor code. For the reliability of the predictive models, the models were analyzed and compared to the experimental industrial combustor research. Finally, the CRN models have shown to be efficient estimating accurately NOx emissions with a very short response time.